Anybody can do anything - MacDonald, Betty Bard (Seattle University of Washington Press, 2016)
"After surviving the failed chicken farm-and marriage-immortalized in The Egg and I, Betty MacDonald returns to live with her mother and desperately searches to find a job to support her two young daughters. Anybody Can Do Anything recounts Betty's hilarious attempts to find work during the Great Depression, all with the help of her older sister Mary"--Cover page 4.
Originally published in 1950.
108112
Keywords: MacDonald, Betty Bard; 1900-1999; Sisters; Depressions -- 1929. -- United States; Authors, American -- 20th century -- Biography; Washington (State); Autobiographies; Biographies